Article On the Methodology of Teaching General Subjects Using Interactive Methods - Kenjayev Anvar Sattorovich (Genius Journals, 2021)
The educational strategy has been changed and its main purpose has become bringing up of free, active, informed and responsible citizens, equipped with the skills of critical thinking and loyal to the modern democratic community in order to meet the demands of present-day democratic society
Keywords: Interactive Teaching; traditional methods; teacher’s role; responsible